Neuropsychological evaluation of the child - Baron, Ida Sue (Oxford University Press, 2004)
Compiles published and previously unpublished normative data for the neuropsychological tests that are most commonly used with children. Integrates concepts and models central to the neuropsychological assessment of children into the discussions of data.